A practical strategy of electrospun fibers of polystyrene/cellulose acetate blend for atmospheric water harvesting - Somoweldeen Abosedira; Moataz Soliman; Shaker Ebrahim; Eman Fadl; Marwa Khalil (Alexandria Engineering Journal)
Atmospheric water harvesting (AWH) is an innovative and sustainable approach to deal with the expanding problem of water scarcity. Herein, the objective is to apply electrospun fiber through blended polymers of cellulose acetate (CA)/polystyrene (PS) with various ratios for collecting the water vapor from the atmosphere. A new prototype for AWH was implemented based on Peltier device. The prepared membranes were characterized by Fourier transforms infrared spectroscopy (FTIR), thermal gravimetric analysis (TGA), and scanning electron microscopy (SEM) and hydrophilicity/hydrophobicity measurement. In CA/PS blend with a ratio of 1:1, SEM image illustrated homogenous, fine and small fibers with an average diameter 100 nm. The presence of CA increases water uptake compared to pure PS. This blend offers a moderate performance in water harvesting, with some water beads potentially forming on the PS fibers and being absorbed by the adjacent CA fibers. In 1:2 blend had a predominance of smooth and small fibers with 100 nm diameter without beads. To enhance the effectiveness of atmospheric water collection, a thermoelectric device (Peltier) in a new well-designed sealed chamber was employed. The efficiency of blended fibers of ratio 1:2 for CA/PS accomplished a collected water of 61.9 mg/cm2.hr with a contact angle of 124.7°.